Local high-concentration electrolyte of lithium metal battery capable of realizing high energy density and long cycle life as well as preparation method and application of local high-concentration electrolyte

By using local high-concentration electrolytes in lithium metal batteries, including lithium salts, ether solvents and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether diluents, a stable and solid SEI film and dense and uniform lithium deposition are formed, the problem of short cycle life of lithium metal batteries is solved, and the effects of high energy density and long cycle life are achieved.

CN119627227AActive Publication Date: 2025-03-14ZHENGZHOU UNIV

Patent Information

Application Number
CN202411946991.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

Lithium metal batteries have problems such as increased battery impedance, rapid attenuation of capacity, and short cycle life due to disordered growth of lithium dendrites of negative electrodes and rapid consumption of electrolytes.

Method used

Using a local high concentration electrolyte, including lithium salt, ether solvent and diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, the formation of a stable and solid SEI film is promoted to achieve dense and uniform deposition of lithium metal by forming a solvation structure mainly composed of contact ion pairs/aggregated ion pairs.

Benefits of technology

It significantly improves the circulation performance of lithium metal batteries, and can achieve 500 stable cycles under the coupling conditions of ultra-high load positive electrode and thin lithium negative electrode, with an average Coulomb efficiency of more than 99.9%, and achieves an energy density of 500 Wh/kg and long cycle life in lithium metal soft-pack batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119627227A_ABST
    Figure CN119627227A_ABST
Patent Text Reader

Abstract

According to the local high-concentration electrolyte of the lithium metal battery capable of realizing high energy density and long cycle life as well as the preparation method and the application of the local high-concentration electrolyte, the viscosity is reduced through the 1, 1, 2, 3, 3, 3-hexafluoropropyl-2, 2, 2-trifluoroether diluent, the wettability of the electrolyte is improved, and meanwhile, the 1, 1, 2, 3, 3, 3-hexafluoropropyl-2, 2, 2-trifluoroether diluent enters a Li < + > solvation shell layer, so that the lithium metal battery can be prepared. The oxygenolysis of solvent molecules is inhibited. In addition, uniform deposition of lithium metal is promoted, a firm and stable SEI film is formed, and side reaction of the electrode and electrolyte is inhibited; the stable long circulation capability of the lithium metal battery is enhanced, 500 times of stable long circulation of the lithium metal battery at 25 DEG C can be realized under the coupling condition of an ultrahigh-load positive electrode (-20 mg / cm < 2 >) and a thin lithium negative electrode (50 microns), and the average coulombic efficiency exceeds 99.9%. The local high-concentration electrolyte enables a 500 Wh / kg lithium metal soft package battery to stably circulate for 90 times at 25 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a local high-concentration electrolyte capable of realizing a lithium metal battery with high energy density and long cycle life, and a preparation method and application thereof. Background Art

[0002] In the context of global advocacy of sustainable development, the development and application of green and environmentally friendly energy storage technology has become an inevitable trend. Lithium-ion batteries have the advantages of no memory effect, no toxic / harmful substances, and recyclability. Compared with traditional batteries, they are more environmentally friendly and meet the requirements of sustainable development. However, the energy density of lithium-ion battery systems based on graphite anodes has reached its theoretical limit (<300 Wh / kg), so there is an urgent need to improve the energy density of the next generation of battery systems and develop new high-energy density batteries. Lithium metal batteries (LMBs) are considered to be a promising alternative, combining ultra-thin lithium metal anodes (<50 μm) with high-voltage cathodes (such as LiNi 0.8 Mn 0.1 Co 0.1 O2, abbreviated as NMC811), the energy density of lithium metal batteries can be increased to more than 400 Wh / kg. However, when it comes to practical applications, lithium metal batteries still face key problems such as increased battery impedance, rapid capacity decay, and short cycle life due to the disordered growth of negative electrode lithium dendrites and rapid consumption of electrolyte. First, compared with traditional graphite negative electrodes, there are more and uncontrollable side reactions between lithium metal negative electrodes and traditional electrolytes, which makes the battery coulomb efficiency low; secondly, the lithium metal negative electrode has a huge volume change during the cycle, which makes the solid electrolyte interface film (SEI) easy to break and repeatedly generate during the cycle, which will consume a lot of electrolyte and shorten the battery life. In addition, the uneven deposition / stripping behavior of the lithium metal negative electrode interface will cause the continuous growth of dendrites and the formation of "dead lithium", resulting in battery short circuit and safety hazards.

[0003] High-performance electrolytes are the key to achieving stable cycling of lithium metal anodes, and finding electrolytes that are compatible with positive and negative electrodes is essential for the development of high-energy-density, long-cycle-life lithium metal batteries. Thermodynamically, no liquid electrolyte is stable due to the low electronegativity of lithium metal. However, when a passivation layer is formed at the interface between the lithium anode and the electrolyte, the electrochemical window can be widened and the lithium metal anode can be dynamically stabilized. Since the lithium metal anode with ultra-high reducibility inevitably reacts with the electrolyte to form SEI, it is crucial to form a suitable and highly stable SEI layer on the lithium metal anode, which can prevent further side reactions between the electrolyte and the lithium anode.

[0004] The researchers proposed some new strategies, including increasing the salt concentration of the electrolyte, designing new fluorinated solvent molecules, and introducing functional additives, to broaden the electrochemical window of the electrolyte and improve its electrochemical stability. These new electrolytes can make the SEI film more stable and uniform, and the deposited lithium particles are larger and denser, which effectively inhibits the formation of "dead lithium" and greatly improves the coulombic efficiency of the negative electrode. However, based on the currently reported electrolytes, and using a high-load positive electrode and a thin lithium negative electrode, the stable cycle number of the resulting lithium metal battery is still less than 300 times, which is still a large gap from practical applications. Summary of the invention

[0006] To solve the above problems, the present invention provides a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, as well as a preparation method and application thereof. By adding a diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, the solvation structure of lithium ions is participated in to form a solvation structure mainly composed of contact ion pairs / aggregated ion pairs, thereby promoting the formation of a stable and strong SEI film, and at the same time achieving dense and uniform deposition of lithium metal, thereby significantly improving the cycle performance of the lithium metal battery.

[0007] The object of the present invention is achieved in the following manner: a local high-concentration electrolyte for a lithium metal battery that can achieve high energy density and long cycle life, comprising a lithium salt, an ether solvent, and a diluent, wherein the diluent is 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether (abbreviated as HTE).

[0008] The lithium salt is lithium bis(fluorosulfonyl)imide (abbreviated as LiFSI), and the ether solvent is ethylene glycol dimethyl ether (abbreviated as DME).

[0009] The molar concentration range of the lithium salt is 1.4~1.7 mol / L; the molar ratio of the ether solvent and the diluent is (1~2):3.

[0010] A method for preparing a local high-concentration electrolyte for a lithium metal battery having high energy density and long cycle life, comprising the following steps: Under a protective atmosphere, the lithium salt is dissolved in an ether solvent, a diluent is then added, and magnetic stirring is performed until the mixture is uniform to obtain a local high-concentration electrolyte.

[0011] The invention discloses an application of a local high-concentration electrolyte in a lithium metal battery, which can realize a high-energy-density and long-cycle-life lithium metal battery.

[0012] A lithium metal battery comprises a positive electrode, a negative electrode and the local high-concentration electrolyte, wherein the positive electrode is a nickel-cobalt-manganese layered oxide and the negative electrode is lithium metal.

[0013] Nickel-cobalt-manganese layered oxide is LiNi 0.8Mn 0.1 Co 0.1 O2.

[0014] A lithium metal soft pack battery comprises a positive electrode, a negative electrode and a local high concentration electrolyte of the lithium metal battery, wherein the positive electrode is a nickel cobalt manganese layered oxide and the negative electrode is lithium metal. The nickel cobalt manganese layered oxide is LiNi 0.83 Mn 0.05 Co 0.12 O2 (abbreviated as Ni83).

[0015] Compared with the prior art, the beneficial effects of the present invention are: (1) The addition of 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether diluent effectively reduces the viscosity of the electrolyte, improves the wettability and ion transport capacity of the electrolyte, and broadens the electrochemical window; (2) Uniform and dense lithium deposition can be achieved. At the same time, salt anions first decompose to form an SEI film rich in inorganic products. This strong and stable negative electrode / electrolyte interface can reduce the occurrence of side reactions and electrolyte consumption, thereby improving the battery's cycle performance.

[0016] (3) At ultra-high positive electrode loading (~20 mg / cm 2 ) coupled with a thin lithium anode (50 μm), the assembled lithium metal battery can achieve 500 stable cycles at 25°C, with an average coulombic efficiency of more than 99.9%.

[0017] (4) At ultra-high positive electrode loading (~25 mg / cm 2 ) coupled with a thin lithium anode (20 μm), the energy density of the assembled lithium metal soft-pack battery can be as high as 500 Wh / kg, and the capacity retention rate after 50 cycles at 25°C is 99.02%, and the capacity retention rate after 90 cycles is 79.08%.

[0018] The local high-concentration electrolyte provided in the present application can realize high-energy density and long cycle life lithium metal batteries. By adding the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether, it participates in the solvation structure of lithium ions, forms a solvation structure mainly composed of contact ion pairs / aggregated ion pairs, promotes the formation of a stable and strong SEI film, and at the same time realizes the dense and uniform deposition of lithium metal, significantly improving the cycle performance of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The cycle performance of the NMC811 || Li battery prepared in Example 1 and Comparative Example 1 at 25°C and 2.7-4.4 V. A is the coulombic efficiency curve of Example 1, B is the specific capacity curve of Example 1, C is the coulombic efficiency curve of Comparative Example 1, and D is the specific capacity curve of Comparative Example 1.

[0020] Figure 2 The cycling performance of the NMC811 || Li battery at 25°C and 2.7-4.4 V for the lithium metal batteries prepared in Example 1 and Comparative Example 2; wherein A is the coulombic efficiency curve of Example 1, B is the specific capacity curve of Example 1, C is the coulombic efficiency curve of Comparative Example 2, and D are the specific capacity curves of Comparative Example 2.

[0021] Figure 3 From top to bottom, Figure A, Figure B, and Figure C are the charge and discharge curves of the NMC811 || Li battery prepared in Example 1, Comparative Example 2, and Example 1 at 25°C and 2.7~4.4 V.

[0022] Figure 4 From top to bottom, Figure A, Figure B, and Figure C are scanning electron microscope cross-sectional views of lithium deposition of Comparative Example 1, Comparative Example 2, and Example 1, respectively.

[0023] Figure 5 The cycling performance of the Ni83||Li battery at 25°C and 2.7-4.4 V for the lithium metal soft-pack battery prepared in Example 1, wherein A is the coulombic efficiency curve of Example 1, and B is the discharge capacity curve of Example 1. DETAILED DESCRIPTION

[0024] A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises a lithium salt, an ether solvent and a diluent, wherein the diluent is 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether.

[0025] The lithium salt is a mixture of one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium trifluoromethanesulfonate, lithium bis(oxalato)difluorophosphate, lithium bis(trifluoromethyl)difluoroborate, and lithium bis(malonate)borate. The ether solvent is at least one of ethylene glycol dimethyl ether, ethylene glycol monobutyl ether, methyl tert-butyl ether, diphenyl ether, and diethylene glycol monomethyl ether.

[0026] Preferably, the lithium salt is lithium bis(fluorosulfonyl)imide, and the ether solvent is ethylene glycol dimethyl ether.

[0027] The molar concentration range of the lithium salt is 1.4~1.7 mol / L; the molar ratio of the ether solvent and the diluent is (1~2):3.

[0028] A method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: under a protective atmosphere, dissolving a lithium salt in an ether solvent, adding a diluent, and magnetically stirring until the mixture is uniform to obtain a local high-concentration electrolyte.

[0029] If the ether solvent and diluent contain water, molecular sieves can be added for adsorption purification to reduce the water content of the ether solvent and diluent to less than 20 ppm.

[0030] The invention discloses an application of a local high-concentration electrolyte in a lithium metal battery that can realize a high-energy density and long cycle life lithium metal battery. The lithium metal battery is a Cu||Li battery, a NMC811||Li battery, or a Ni83||Li battery.

[0031] A lithium metal battery comprises a positive electrode, a negative electrode and the local high concentration electrolyte, wherein the positive electrode is a nickel-cobalt-manganese layered oxide and the negative electrode is lithium metal. The nickel-cobalt-manganese layered oxide can be LiNi 0.8 Mn 0.1 Co 0.1 O2.

[0032] A lithium metal soft pack battery comprises a positive electrode, a negative electrode and a local high concentration electrolyte for realizing a lithium metal battery with high energy density and long cycle life, wherein the positive electrode is a nickel cobalt manganese layered oxide and the negative electrode is lithium metal. The nickel cobalt manganese layered oxide can be LiNi 0.83 Mn 0.05 Co 0.12 O2.

[0033] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that this embodiment is only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Technical personnel skilled in the art can make some non-essential improvements and adjustments based on the above-mentioned contents of the present invention.

[0034] Sources of raw materials in the examples and comparative examples of this application: Comparative Example 1 is a finished commercial electrolyte, purchased from Suzhou Duoduo Chemical Technology Co., Ltd.; the lithium salt lithium bis(fluorosulfonyl)imide (LiFSI) in Comparative Example 2 and the examples was purchased from Tokyo Chemical Industry Co., Ltd. (TCI), the solvent ethylene glycol dimethyl ether (DME) was purchased from Sinopharm Group Co., Ltd., the diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE) was purchased from Suzhou Duoduo Chemical Technology Co., Ltd., and the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether (HTE) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0035] The glove box was purchased from Weige Technology (Suzhou) Co., Ltd., the magnetic stirrer was purchased from Shanghai Heyue Instrument Co., Ltd., the battery shell and diaphragm were purchased from Kruder Laboratory Equipment Technology Co., Ltd., the positive electrode material was purchased from Fulin Precision Co., Ltd., and the lithium-copper composite belt was purchased from Tianjin Zhongneng Lithium Co., Ltd. All batteries were tested using the Blue Electric Battery Testing System.

[0036] Example 1 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:1.2:3.

[0037] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt was dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt was completely dissolved at a stirring speed of 400 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether was added and magnetic stirring was continued until the mixture was evenly mixed to obtain a locally high-concentration electrolyte. The total stirring time was 4 hours.

[0038] Comparative Example 1 Common commercial lithium metal battery electrolyte, purchased from Suzhou Duoduo Chemical Technology Co., Ltd., the raw materials are lithium salt, solvent and additives; among them: The lithium salt is lithium hexafluorophosphate (LiPF6) with a molar concentration of 1.0 mol / L.

[0039] The solvents are ethylene carbonate (EC) and ethyl methyl carbonate (EMC), and the volume ratio of the two is 3:7.

[0040] The additive is vinylene carbonate (VC), and the addition amount is 2%.

[0041] Comparative Example 2 Common local high concentration electrolytes for lithium metal batteries, the raw materials are lithium salts, solvents and diluents; among them: The lithium salt is lithium bis(fluorosulfonyl)imide (LiFSI) with a molar concentration of 1.74 mol / L.

[0042] The solvent was dimethyl ether (DME).

[0043] The diluent is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).

[0044] The molar ratio of LiFSI, DME and TTE is 1:1.2:3.

[0045] In a glove box filled with argon atmosphere, lithium salt is first dissolved in DME, and then the diluent TTE is added. After magnetic stirring and mixing, a local high-concentration electrolyte is obtained.

[0046] Example 1, Comparative Example 1 and Comparative Example 2 are all used to assemble 2016-type button batteries and perform performance tests: (1) NMC811 || Li battery: In the lithium metal battery, a lithium copper composite strip with a thickness of 50 μm is selected as the negative electrode, with a loading of 20 mg / cm 2 LiNi 0.8 Mn 0.1 Co 0.1 O2 (NMC811) is the positive electrode, the diaphragm is a 20 μm thick PP / PE / PP diaphragm, and the electrolyte consumption for each battery is 100 μL.

[0047] The electrolytes of Example 1, Comparative Example 1 and Comparative Example 2 were respectively used for NMC811 || Li battery for cycle performance test. The test conditions were as follows: at 25°C, the battery was charged to 4.4 V at a constant current rate of 0.1C (1C=200 mAh / g), and then discharged to 2.7 V at a constant current rate of 0.1C. After 2 cycles, the battery was charged to 4.4 V at a constant current rate of 0.1C again, and then discharged to 2.7 V at 0.33C.

[0048] (2) Cu||Li battery: A 50 μm thick lithium-copper composite strip is used as the negative electrode, an 8 μm thick Cu foil is used as the positive electrode, and a 20 μm thick PP / PE / PP separator is used as the separator. The amount of electrolyte used for each battery is 100 μL.

[0049] The electrolytes of Example 1, Comparative Example 1 and Comparative Example 2 were used in Cu||Li batteries for testing respectively. The testing conditions were: at 25°C and at 0.5 mA / cm 2 The current density was constant current charged for 8 hours.

[0050] (3) Lithium metal soft pack battery Ni83 || Li battery: In the lithium metal battery, a lithium copper composite tape with a thickness of 20 μm is used as the negative electrode, with a loading of 25 mg / cm 2 Ni83 is used as the positive electrode, and the diaphragm is a 20 μm thick PP / PE / PP diaphragm. The battery capacity is 6 Ah, the E / C ratio is 1.2 g / Ah, and the energy density is 500 Wh / kg.

[0051] The electrolyte of Example 1 was used for testing the lithium metal soft-pack battery Ni83 || Li battery. The test conditions were as follows: at 25°C, the battery was charged to 4.4 V at a constant current rate of 0.1C (1C = 200 mAh / g), and then discharged to 2.7 V at a constant current rate of 0.1C. After 2 cycles, the battery was charged to 4.4 V at a constant current rate of 0.1C again, and then discharged to 2.7 V at 0.33C.

[0052] Test results: (1) The electrolyte prepared in Example 1 was used to test the cycle performance of NMC811 || Li battery. The test results are as follows: Figure 1 and Figure 2 As shown, it can be stably cycled for 500 times with a capacity retention rate of 66.03%.

[0053] The electrolyte of comparative example 1 was used for NMC811||Li battery to carry out cycle performance test. The test results are as follows: Figure 1 As shown, comparative example 1 can only stably cycle 200 times before the capacity rapidly decays. Example 1 of the present application is used for NMC811||Li battery cycle performance test, and can stably cycle 500 times, with a capacity retention rate of 66.03%, and the capacity is always better than comparative example 1 during the cycle process.

[0054] The electrolyte of comparative example 2 was used for NMC811||Li battery to carry out cycle performance test. The test results are as follows: Figure 2 As shown, comparative example 2 can stably cycle 350 times before capacity fluctuation occurs, and then the battery fails. Example 1 of the present application is used for NMC811||Li battery cycle performance test, which can stably cycle 500 times, with a capacity retention rate of 66.03%, and the capacity is always better than comparative example 2 during the cycle process.

[0055] The electrolyte prepared in Comparative Example 1, Comparative Example 2 and Example 1 is used for charging and discharging of NMC811||Li batteries, such as Figure 3 As shown, the capacity of Comparative Example 1 decays slowly in the first 150 cycles, and the polarization increases rapidly after 150 cycles, accompanied by a capacity dive; the capacity difference between Comparative Example 2 and Example 1 is not much in the first 300 cycles, and after 300 cycles, the polarization of Comparative Example 2 increases significantly accompanied by a rapid capacity decay, thereby causing battery failure, while the capacity of Example 1 decays slowly and can ensure stable cycles for 500 times.

[0056] (2) After deposition of 4 mAh / cm in a Cu||Li battery 2 The scanning electron microscope image results are as follows Figure 4As shown, the thickness of lithium deposited in Comparative Example 1, Comparative Example 2, and Example 1 is approximately 108 μm, 32 μm, and 30 μm, respectively. The lithium deposition in Comparative Example 1 is the thickest, and there are many voids, and its ability to deposit / strip lithium is poor. However, Example 1 obtains the thinnest and densest lithium metal deposition, indicating that it has excellent ability to deposit / strip lithium.

[0057] (3) The electrolyte prepared in Example 1 was used for the lithium metal soft pack battery Ni83||Li battery to carry out the cycle performance test. The test results are as follows: Figure 5 As shown, the capacity retention rate after 50 cycles at 25°C is 99.02%, and the capacity retention rate after 90 cycles is 79.08%.

[0058] The embodiments of the present application may also be the following embodiments: Example 2 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:1:3.

[0059] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt is dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt is completely dissolved. The stirring speed is usually 380 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is added and magnetic stirring is continued until the mixture is evenly mixed to obtain a locally high-concentration electrolyte.

[0060] Example 3 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:1.4:3.

[0061] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt is dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt is completely dissolved. The stirring speed is usually 420 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is added and magnetic stirring is continued until the mixture is evenly mixed to obtain a locally high-concentration electrolyte.

[0062] Example 4 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:1.6:3.

[0063] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt is dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt is completely dissolved. The stirring speed is usually 400 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is added and magnetic stirring is continued until the mixture is evenly mixed to obtain a locally high-concentration electrolyte.

[0064] Example 5 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:1.8:3.

[0065] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt is dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt is completely dissolved. The stirring speed is usually 380 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is added and magnetic stirring is continued until the mixture is evenly mixed to obtain a locally high-concentration electrolyte.

[0066] Example 6 A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, comprising lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether; the molar ratio of lithium bis(fluorosulfonyl)imide (LiFSI), ethylene glycol dimethyl ether (DME), and 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is 1:2:3.

[0067] The method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life comprises the following steps: In a glove box filled with argon atmosphere, lithium salt is dissolved in solvent ethylene glycol dimethyl ether and magnetically stirred until the lithium salt is completely dissolved. The stirring speed is usually 400 rpm. Then, the diluent 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether is added and magnetically stirred until the mixture is evenly mixed to obtain a locally high-concentration electrolyte.

[0068] The invention provides a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life. The electrolyte reduces viscosity and improves electrolyte wetting performance by using 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether diluent. Meanwhile, the 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether diluent enters the Li + The solvation shell inhibits the oxidative decomposition of solvent molecules. In addition, it promotes the uniform deposition of lithium metal, forms a strong and stable SEI film, inhibits the side reaction between the electrode and the electrolyte, and enhances the stable long-cycle ability of lithium metal batteries. 2 ) coupled with a thin lithium anode (50 μm), the lithium metal battery can achieve 500 stable long cycles at 25°C, with an average coulombic efficiency of more than 99.9%. This local high-concentration electrolyte enables a 500 Wh / kg lithium metal soft-pack battery to be stably cycled 90 times at 25°C.

[0069] The above description is only a preferred embodiment of the present invention, but the protection scope of the present invention is not limited thereto. It should be pointed out that for those skilled in the art and any technician familiar with the technical field, without departing from the overall concept of the present invention, the technical solution and the inventive concept of the present invention are equivalently replaced or changed, and several changes and improvements are made, which should also be regarded as the protection scope of the present invention.

Claims

1. A local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life, characterized in that: The invention comprises lithium salt, ether solvent and diluent, wherein the diluent is 1,1,2,3,3,3-hexafluoropropyl-2,2,2-trifluoroethyl ether.

2. The local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life according to claim 1, characterized in that: The lithium salt is lithium bis(fluorosulfonyl)imide, and the ether solvent is ethylene glycol dimethyl ether.

3. The local high concentration electrolyte for realizing high energy density and long cycle life lithium metal battery according to claim 1 or 2, characterized in that: The molar concentration of the lithium salt is 1.4~1.7 mol / L; the molar ratio of the ether solvent and the diluent is (1~2):

3.

4. A method for preparing a local high-concentration electrolyte for a lithium metal battery with high energy density and long cycle life according to any one of claims 1 to 3, characterized in that: The following steps are involved: Under a protective atmosphere, the lithium salt is completely dissolved in an ether solvent, a diluent is then added, and magnetic stirring is performed until the mixture is uniform to obtain a locally high-concentration electrolyte.

5. Application of a local high-concentration electrolyte in lithium metal batteries that can achieve high energy density and long cycle life.

6. A lithium metal battery, characterized in that: The invention comprises a positive electrode, a negative electrode and the local high concentration electrolyte as claimed in any one of claims 1 to 4, wherein the positive electrode is a nickel-cobalt-manganese layered oxide and the negative electrode is lithium metal.

7. The lithium metal battery according to claim 6, characterized in that: Nickel-cobalt-manganese layered oxide is LiNi 0.8 Mn 0.1 Co 0.1 O2.

8. A lithium metal soft pack battery, comprising a positive electrode, a negative electrode and a local high concentration electrolyte for realizing a lithium metal battery with high energy density and long cycle life as claimed in any one of claims 1 to 4, wherein: The positive electrode is a nickel-cobalt-manganese layered oxide, and the negative electrode is lithium metal; the nickel-cobalt-manganese layered oxide is LiNi 0.83 Mn 0.05 Co 0.12 O2.

Citation Information

Patent Citations

  • Electrolyte and lithium ion battery

    CN118073654A

  • Lithium metal battery electrolyte and lithium metal battery

    CN118336115A

  • Electrolyte for lithium secondary battery and lithium secondary battery comprising thereof

    KR1020180117868A

  • KR20210115319A

Cited By

  • Electrolyte for high-specific-energy lithium metal battery and lithium metal battery

    CN120749233A